PENGARUH PEMBERIAN FLY ASH DAN PUPUK KOTORAN AYAMTERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell.Arg)PADA TANAH GAMBUT - Lisa Liani; Beny Setiawan Beny Setiawan; Nurhayati Nurhayati (Journal of Agro Plantation (JAP), 2025)
Fly ash is used as an ameliorant to neutralize sapric peat soil and as an additional nutrientneeded by plants, but still plants grown in peat media require appropriate fertilization, namely organicfertilizer so that the plants are always met for their nutrient needs. The provision of organic fertilizer canimprove the structure of the soil that is very deficient in organic elements and can strengthen plant roots.This study aims to determine the effect of the growth of rubber seedlings (Hevea brasilliensis Muel. Arg)due to the application of fly ash and chicken manure on peat soil. This study used a factorial CompletelyRandomized Design (CRD), where the first factor was fly ash with 3 treatments and the second factor was  chicken manure with 3 treatments so that 9 treatment combinations were obtained. Observationparameters included soil pH, plant height (cm), number of umbrellas (strands), stem diameter (cm), rootlength (cm). The data obtained were analyzed using Analysis of Variance (ANOVA). If the data obtainedhad a significant effect, then the Duncan Multiple Range Test (DMRT) was carried out at the 5% level.The results showed that the provision of fly ash dose of 100 g/polybag was the best dose that affected thevegetative growth of plants on the parameters of plant height (49.56 cm), stem diameter (4.01 mm) andthe provision of a dose of 150 g/polybag on the parameters of the number of umbrellas (3 strands) androot length (33.09 cm) at 13 WAP. The provision of a dose of 500 g/polybag on chicken manure fertilizerwas the best dose that affected plant growth on the parameters of plant height (53.40 cm), stem diameter(4.36 mm), number of umbrellas (3 strands) and root length (31.03 cm) at 13 WAP. The interaction of flyash treatment 150 g/polybag and chicken manure fertilizer 500 g/polybag had a significant effect on allobservation parameters on peat soil.